Recent advances in teaching–learning methodologies of the Ayurveda education system - Bhagyashree Jibkate; Akshay S. Pargaonkar (Journal of Education and Health Promotion)
Teaching and learning are two sides of the same coin. Ayurveda, the ancient system of medicine that originated in India, has a long history of teaching and learning methods. In the early days, Ayurvedic knowledge was primarily transmitted through oral tradition, with teachers passing down their knowledge to students through direct communication. Ayurvedic education is increasingly becoming extra-oriented. The current educational system is upgraded by various teaching–learning technologies tovarious factors. The upshot of this is a student-centered outcome. Hence, systematical examination and analysis ofrecent advances in Ayurveda teaching and learning methods is the primary objective of this review. These modern methods complement traditional Ayurvedic teachings, providing students with a well-rounded education that combines ancient wisdom with contemporary technology. The integration of these technologies aims to make Ayurvedic education more dynamic, accessible, and relevant to the evolving needs of students and the healthcare landscape. These methods contribute to the evolution of Ayurvedic education while protecting the fundamental principles and wisdom of Ayurveda.